Reopening of Surabaya Zoo in Coronavirus Disease 2019 (Covid-19) Pandemic - Puteri Hapsari Fitriyanti (Airlangga Development Journal, 2021)
High spread of Covid-19 in Surabaya implemented on a Large-Scale Social Restrictions policy. This has impacted on closure of tourist destinations, including Surabaya Zoo. During the closing period, Surabaya Zoo suffered significant losses due to the absence of revenue that impacted on the conservation operations in saving endangered animals. Based on Surabaya Mayor Regulation of New Normal Order Guidelines Number 28 of 2020 as amended by Number 33 of  2020, Surabaya Zoo is reopened. This fact is an interesting issue to study how well the management in handling this situation. The writing method used in this paper is a literature review and primary data collection as a form of best practice that might be adopted in Surabaya Zoo. The results showed that management is succeeded in reopening Surabaya Zoo. The conclusion from this study is Surabaya Zoo is recommended to be reopened during the first stage of New Normal